Analysis of data of dependence between parameters of transmission channel model - Муранов, А. С.; Чуприн, В. М.; Кочергін, Ю. А. (Problems of Informatization and Control, 2008)
Performed the dependency analysis of data transmission channel model parameters influence on quality functioning. It is demonstrated that one-channel devices with sequential elementary signals transmission possess an advantage over the parallel signals data transmission. In the category of incoherent systems in the range of specific rates 0,5 - 1,5 (bit/s)/Hz the most effective are the devices with AFPM data transmission. Intersystem interference, which is caused by the final AFC channel width, is the crucial factor that hinders and decreases device interference immunity. It is also demonstrated that AFPM exceeds by its quality characteristics FM and PDM in the range of specific rates 0,5 - 1,8 (bit/s)/Hz. The capacity or number of signals transmission beneficial coefficient’s meaning of F lies in the following range 1,3 - 5 (Р≈ехр(-αF), where α=h2/2R). With the increasing of specific rates beneficial coefficient F decreases